Review of marketing research special issue : marketing legends - Naresh K. Malhotra (Review of marketing research,, 2011)
This volume will feature the work of Marketing Legends that have been announced so far. Each Legend will describe his contributions to the marketing discipline: Richard Bagozzi; Shelby Hunt; Philip Kotler; V. Kumar; Naresh K. Malhotra; Kent Monroe; Jagdish Sheth; Jerry Wind; Gerald Zaltman.